Cases in public relations strategy - St. John, Burton 1957-; Martinelli, Diana Knott; Pritchard, Robert S.; Spaulding, Cylor (SAGE Publications, Inc, 2019)
Cases in Public Relations Strategy draws on original, real-world case studies to provide students with a strategic approach to meeting the needs of a client before, during, and beyond a campaign. Using the RACE (Research, Action Planning, Communication, and Evaluation) model, students explore successful contemporary campaigns and evaluate best practices in all major areas of public relations activity. This practical, client-oriented text shows students how to systematically evaluate and adapt to the needs of a particular client-whether big or small, global or local, for-profit or nonprofit-in order to launch the most effective campaign. Each case includes a brief introduction focused on fundamentals and core competencies, and all cases have been carefully selected to present a wide range of client types. In addition to the lessons from professionals in the case studies, a section on PR consulting and an appendix on advancing your PR career give students the knowledge and skills they need for success in the field. Give your students the SAGE edge! SAGE edge offers a robust online environment featuring an impressive array of free tools and resources for review, study, and further exploration, keeping both instructors and students on the cutting edge of teaching and learning. Learn more at edge.sagepub.com/stjohn.